Distribution of Iron Uptake Systems Encoding Genes Among the Clinical Isolates of Escherichia coli Compared to Foodstuffs Isolates - Mahmoudi, Hassan; Hossainpour, Hadi; Moradi, Mohammad; Alikhani, Mohammad Y. (Infectious Disorders - Drug Targets, 2020)
Introduction: Bacteria require iron ions to grow and infect the host, which, by using iron uptake systems, acquire free iron from their host cell. Escherichia coli is one of the most important pathogens to cause food poisoning and clinical infections. The aim of this study was to assess the distribution of iron uptake systems encoding genes in clinical isolates of E.coli compared to food samples isolates. Materials and Methods: This investigation was conducted to determine the prevalence of E. coli isolated from various sources of food and clinical specimens. The E. coli isolates confirmed by the standard microbiological methods. The isolates were examined for the presence of iut A and iuc A genes by specific primers using the polymerase chain reaction technique. Results: A total of 100 and 50 isolates of E. coli were collected from clinical samples and foodstuffs, respectively. The prevalence of E. coli in the food and clinical samples was 33.33% and 64.10%, respectively. The frequency of iut A and iuc A genes in the food and clinical isolates were 76%-84% and 86% - 83%, respectively. Conclusion: Our results showed that the prevalence of E. coli isolates with iut A and iuc A genes was relatively higher compared to many previous studies. The existence of these genes in E. coli strains is likely to be related to pathogenicity in those strains, which requires further studies in the future.
Keywords: foodstuffs isolates